PTH-340 Complete pathological tumour response and outcomes in indian patients with rectal cancers. (22nd June 2015) - Sinukumar, S; Saklani, A; Engineer, R; Patil, P
Abstract : Introduction: Total Mesorectal Excision coupled with neoadjuvant chemoradiotherapy (NACTRT) is currently considered the standard treatment for patients with locally advanced rectal cancers (LARC). Various studies have reported pathological downstaging and a complete pathological response rate of 15% >27% following neoadjuvant chemoradiotherapy which has translated into improved survival. We endeavour to determine the clinical outcome of patients attaining a complete pathological tumour response following neoadjuvant chemoradiotherapy in the Indian setting where most of our patient population is younger and present with aggressive tumour biology. Method: Four hundred and thirty patients of LARC underwent surgical resection following NACTRT from 2010 to 2013. Of the 430 patients, seventy patients achieved complete pathological response in the primary tumour. Clinicopathological and treatment details were recorded for these 70 patients. Locoregional and systemic recurrence rates were calculated and Disease free survival (DFS), Overall survival (OS), were evaluated using Kaplan-Meier curves. Log-rank test was used to compare survival outcomes between different subgroups of patients. Results: 16.2% patients had a complete pathological tumour response (ypT0). The median age of presentation was 47 years (Range 18–77 years). The median pretreatment carcinoembryonic (CEA) tumour marker level was 3.2 (Range 1.1–127 ng/ml). The median interval between completion of NACTRT and surgery was 56 days (Range12–206days). Abdominoperineal resection (APR) was the most common surgical procedure perfomed. The commonest histology was classical adenocarcinoma. Signet cell carcinoma and mucinous carcinoma was seen in 12.8% and 7.1% of cases respectively. The median nodes dissected at surgery was 8(range 1–21). Six out of the 70 patients (8.6%) showed residual disease in the nodes. (ypT0N0=64, ypT0N+ =06). After a median follow up of 30.5 months (Range 11–59 months), the 3 year Overall survival was 95.1% and the 3 year Disease free survival was 87.9% for these 70 patients. In patients with complete response in the tumour but residual disease in nodes, i.e. ypT0N+, the 3year DFS was 80% and OS was 100%. As compared to the above, patients with no residual nodal disease enjoyed a 3 year DFS of 88.5% (Log-rank, p = 0.48) and an OS of 94.6% (Log-Rank, p = 0.58). The locoregional and systemic recurrence rates both were 4.2% respectively. Conclusion: In the Indian scenario, despite younger age and higher proportion of mucinous and signet cell tumours outcome in complete responders is good and is in concordance with world literature. Disclosure of interest: None Declared.